A review of natural fiber reinforced poly(Vinyl alcohol) based composites: application and opportunity - Boon, Khoon Tan; Yern, Chee Ching; Sin, Chew Poh; Chuah, Luqman; Seng, Neon Gan (Multidisciplinary Digital Publishing Institute, 2015)
Natural fibers are fine examples of renewable resources that play an important role in the composites industry, which produces superior strength comparable to synthetic fibers. Poly(vinyl alcohol) (PVA) composites in particular have attracted enormous interest in view of their satisfactory performance, properties and biodegradability. Their performance in many applications such as consumer, biomedical, and agriculture is well defined and promising. This paper reviews the utilization of natural fibers from macro to nanoscale as reinforcement in PVA composites. An overview on the properties, processing methods, biodegradability, and applications of these composites is presented. The advantages arising from chemical and physical modifications of fibers or composites are discussed in terms of improved properties and performance. In addition, proper arrangement of nanocellulose in composites helps to prevent agglomeration and results in a better dispersion. The limitations and challenges of the composites and future works of these bio-composites are also discussed. This review concludes that PVA composites have potential for use in numerous applications. However, issues on technological feasibility, environmental effectiveness, and economic affordability should be considered.